Graphene-induced band gap renormalization in polythiophene: a many-body perturbation study. (15th December 2017) - Marsusi, F; Fedorov, I A; Gerivani, S
Abstract: Density functional theory and many-body perturbation theory at the G0 W0 level are employed to study the electronic properties of polythiophene (PT) adsorbed on the graphene surface. Analysis of the charge density difference shows that substrate-adsorbate interaction leads to a strong physisorption and interfacial electric dipole moment formation. The electrostatic potential displays a  −0.19 eV shift in the graphene work function from its initial value of 4.53 eV, as the result of the interaction. The LDA band gap of the polymer does not show any change. However, the band structure exhibits weak orbital hybridizations resulting from slight overlapping between the polymer and graphene states wave functions. The interfacial polarization effects on the band gap and levels alignment are investigated at the G0 W0 level and show a notable reduction of PT band gap compared to that of the isolated chain.